Penentuan Kualitas Pelayanan Jasa Wisata Dengan Metode Service Quality (Servqual) dan Teoriya Resheniya Izobreatatelskikh Zadatch (TRIZ) - Bayu Wahyu Nirwana; Ari Zaqi Al-Faritsy (CV. KAMPUS AKADEMIK PUBLISING, 2024)
One of the businesses operating in the tourism sector in the city of Yogyakarta is Lava Tour Mjak Jeep Merapi. In this research, there are problems regarding the gap between consumer perceptions and expectations and how to obtain appropriate quality improvements. The aim of this exploration is to find similarities between consumer perceptions and assumptions and to obtain appropriate quality improvements. As an attribute of questionnaire questions, the SERVQUAL method utilizes service dimensions such as realism, reliability, responsiveness, assurance, and empathy. The TRIZ method is used to produce various innovative solutions. The research results show that there are more attributes that have negative GAPs than positive GAPs. With the TRIZ method, several improvements can be made, such as the cleanliness and tidiness of the base camp, employee appearance, responsiveness in dealing with customers, service to customers, as well as improving the availability of adequate equipment. The attribute that has the largest negative GAP value is employees not helping customers with difficulties with a score of -0.18, so this attribute is the main point for improvement in the results of the SERVQUAL method.